LETTINCK, Paul, Aristotle 's Meteorology and its reception in the arab world, With an Edition and Transíation of Ibn Suwar's Treatise on Meteorological Phenomena and Ibn Baija's Comentary on the Meteorology. - Escobar Gómez, Santiago (Anaquel de Estudios Árabes, 1999)
Sin resumen